Semantic Songket Image Search with Cultural Computing of Symbolic Meaning Extraction and Analytical Aggregation of Color and Shape Features - Amirullah, Desi; Barakbah, Ali Ridho; Basuki, Achmad (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
The term